Corporate Responsibility for Violations of Online Consumer Data Privacy - Hendri Khuan; Amin Zaki; Faizal Razak (Rechtsnormen: Journal of Law, 2025)
Background. As digital platforms evolve, consumer privacy concerns related to online data breaches have risen. Companies are increasingly held responsible for the protection of consumer data. The need to assess corporate responsibility in such violations is critical for consumer trust and regulatory frameworks. Objective. This study aims to explore the extent of corporate responsibility in online consumer data privacy violations and the legal and ethical implications for businesses involved. Method. A qualitative research design was adopted, utilizing a case study approach. Relevant case law and reports of data breaches were analyzed to assess how companies manage their data privacy policies and how these are reflected in their accountability for breaches. Background. As digital platforms evolve, consumer privacy concerns related to online data breaches have risen. Companies are increasingly held responsible for the protection of consumer data. The need to assess corporate responsibility in such violations is critical for consumer trust and regulatory frameworks. Objective. This study aims to explore the extent of corporate responsibility in online consumer data privacy violations and the legal and ethical implications for businesses involved. Method. A qualitative research design was adopted, utilizing a case study approach. Relevant case law and reports of data breaches were analyzed to assess how companies manage their data privacy policies and how these are reflected in their accountability for breaches. Results. Findings reveal that while corporations acknowledge the importance of consumer data privacy, there are significant gaps in their implementation of security measures. Legal frameworks often fail to hold companies accountable for breaches, relying instead on self-regulation and fines that are not always sufficient to deter negligence. Conclusion. Corporate responsibility for online data privacy violations requires stronger legal frameworks and stricter enforcement of data protection measures. It is essential for businesses to adopt comprehensive privacy policies and ensure compliance with emerging global standards.